Synthesis, Characterization and Biological Studies of a Mannich Base N-[Phenyl(pyrrolidin-1-yl)methyl]acetamide and Its VO(IV), Mn(II) and Fe(II) Complexes - Muruganandam, L.; Krishna Kumar, K.; Balasubramanian, K. (Asian Journal of Chemistry, 2012)
N-[Phenyl(pyrrolidin-1-yl)methyl]acetamide was synthesized using Mannich reaction. The complexes of oxovanadium(IV), manganese(II) and iron(II) with this Mannich base were prepared and characterized by elemental analysis and spectral measurements. The spectral data reveal that the ligand acts as bidentate coordination to the metal ion through the CNC nitrogen and carbonyl oxygen atoms. Based on the UV spectral and magnetic moment data, octahedral geometry is assigned for all the complexes. The antimicrobial screening shows that the complexes are more active than the ligand.